Herding Cats Revisited : Being More Advice for Aspiring Academic and Research Leaders. - Garrett, Geoff. (Triarchy Press, 2021)
Helps academic/research leaders and aspiring leaders to accept and embrace the qualities of their 'cats' so they can achieve demanding goals with agility.